Complexity of the auxin biosynthetic network in Arabidopsis hypocotyls is revealed by multiple stable-labeled precursors - Tillmann, M.; Tang, Q.; Gardner, G.; Cohen, J. D.
Auxin is a key regulator of plant development and in Arabidopsis thaliana can be synthesized through multiple pathways; however, the contributions of various biosynthetic pathways to specific developmental processes are largely unknown. To trace the involvement of various biosynthetic routes to indole-3-acetic acid (IAA)under conditions that induce adventitious root formation in Arabidopsis hypocotyls, we treated seedlings with three different stable isotope-labeled precursors ([13C6]anthranilate, [15N1]indole, and [13C3]serine)and monitored label incorporation into a number of proposed biosynthesis intermediates as well as IAA. We also employed inhibitors targeting tryptophan aminotransferases and flavin monooxygenases of the IPyA pathway, and treatment with these inhibitors differentially altered the labeling patterns from all three precursors into intermediate compounds and IAA. [13C3]Serine was used to trace utilization of tryptophan (Trp)and downstream intermediates by monitoring 13C incorporation into Trp, indole-3-pyruvic acid (IPyA), and IAA; most 13C incorporation into IAA was eliminated with inhibitor treatments, suggesting Trp-dependent IAA biosynthesis through the IPyA pathway is a dominant contributor to the auxin pool in de-etiolating hypocotyls that can be effectively blocked using chemical inhibitors. Labeling treatment with both [13C6]anthranilate and [15N1]indole simultaneously resulted in higher label incorporation into IAA through [15N1]indole than through [13C6]anthranilate; however, this trend was reversed in the proposed precursors that were monitored, with the majority of isotope label originating from [13C6]anthranilate. An even greater proportion of IAA became [15N1]-labeled compared to [13C6]-labeled in seedlings treated with IPyA pathway inhibitors, suggesting that, when the IPyA pathway is blocked, IAA biosynthesis from labeled indole may also come from an origin independent of the measured pool of Trp in these tissues.
Keywords: ARABIDOPSIS THALIANA; AUXIN; BRASSICACEAE; IAA BIOSYNTHESIS; INDOLE; MOUSE EAR CRESS; PHYTOHORMONES; STABLE ISOTOPES; TARGETED METABOLOMICS; TRYPTOPHAN